Agent-based simulation approach to urban dynamics modeling (2012)
This article presents a general agent-based simulation approach that captures agents’ decision-making processes and dynamic relationships that determine urban shape. The article shows how to simulate urban growth patterns and land-use change dynamics using economic assumptions and by modeling the interactions of computational agents.